Agency Cost dan Persaingan Perusahaan Sektor Non Keuangan Pada Saat Pandemi Covid-19 - Sukoco, Y.Djoko (Fakultas Ekonomi Universitas Kadiri, 2023)
This study examines the effect of agency cost on return on assets (ROA) and investigates the moderating effect of product market competition on the effect of agency cost on firm financial performance by using leverage and firm size as control variables. The purposive sampling method documents as many as 715 research sample data on non-financial companies for the 2020-2022 period. This study proves that agency cost has a negative effect on a company's financial performance and competition moderates the negative effect of agency cost on a company's financial performance.